Skip - Mendoza, Molly (Nobrow, 2022)
When Bloom is thrown from their world and Gloopy is exiled from their home, each finds in the other a much-needed kindred spirit. But as they skip through dimensions among great weeping giants, enormous alligator islands and topsy-turvy 2D worlds, they find that their greatest challenges are in facing their own truths and fears which they have both been anxious to avoid...